Study on the growth factors and hepatoprotective effect of Tamarindus indica L. pulp aqueous extract in male Wistar rats - ALMOLAFIKH, SULTANA TURKI; ALNOURI, DOHA MUSTAFA; ARZOO, SHAISTA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The purpose of this study was to investigate the effect of tamarind juice on growth and liver enzymes. The experiment was conducted on 15 Wistar albino rats, divided into 3 groups. Group 1 was fed with a standard diet (control group), group 2 was fed with a standard diet and 1 ml tamarind extract and group 3 was fed with a standard diet and 2 ml tamarind extract. Statistically insignificant difference was observed between control and experimental groups for total food final weight but it has been found that change in weight was slightly higher in control group when compared to experimental group. When compared to control group, administration of tamarind did not produce any significant changes in AST and ALT activities in serum but it exhibited antiobesity effect. consumption and food efficiency. Similarly difference was insignificant for initial weight and